2016
DOI: 10.5114/reum.2015.57637
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and serological parameters in female and male patients with systemic sclerosis

Abstract: ObjectivesThe course of systemic sclerosis (SSc) can differ in female and male patients. According to the literature the incidence rates of diffuse cutaneous SSc, scleroderma renal crisis and digital ulceration are higher in male patients. The aim of the study was to compare selected clinical and serological parameters in male and female patients with SSc.Material and methodsThe study encompassed 101 European Caucasian patients with SSc, including 23 men, hospitalized in the Department of Rheumatology. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
3
5
0
Order By: Relevance
“…Systemic sclerosis is more common in women than men; however, the course of the disease may be more progressive in men [29]. Similar to other populations, i.e.…”
Section: Discussion_____________________________mentioning
confidence: 58%
“…Systemic sclerosis is more common in women than men; however, the course of the disease may be more progressive in men [29]. Similar to other populations, i.e.…”
Section: Discussion_____________________________mentioning
confidence: 58%
“…Also, the female to male ratio was 1.6 : 1 in Sittichai Netwijitpan’s study on hospitalized patients [ 4 ]. In a study done by Wielosz et al [ 11 ] on European Caucasian patients, this ratio was 3.1 : 1. Although in a study done in Italy (Sardinia) on 4981 hospitalizations in 2001–2012, the women’s admissions was 84.8% that was nearly the same as our patients [ 12 ].…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the majority of the patients had dcSSc (91.03%). Netwijitpan et al [ 4 ] also reported that 81.7% of the hospitalized SSc patients had dcSSc although in a European study the admissions were more in patients with LcSSc [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 In our study, male patients had a higher prevalence of diffuse cutaneous systemic sclerosis, which was in agreement with several other studies. 25,26 The prevalence of anti-topoisomerase-I positivity was high in the present series compared to those in Caucasians, 10,27 Africans, 28 and other Asian 29,30 countries. It was however similar to the rates in the Chinese 31 and Indian 32 populations.…”
Section: Resultsmentioning
confidence: 43%